2017
DOI: 10.1080/1478422x.2017.1294356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anions on corrosion behaviour of carbon steel in simulated groundwater in China

Abstract: Carbon steel is a candidate material for the disposal container of high-level nuclear waste in a deep geological repository in China, which will be subject to general corrosion and localised attack. In this work, the effects of Cl − , SO 4 2-and CO 3 2− concentrations on the general corrosion and crevice corrosion of carbon steel were studied by immersion tests and electrochemical measurements. The results show that Cl − promotes general corrosion, while SO 4 2− and CO 3 2− inhibit general corrosion. In a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It was 250 and 316.6 ppb in bigger and smaller crevices, respectively. Xu et al have reported that ion promotes crevice corrosion in carbon steel more compared to Cl − in single ion solutions whereas; in groundwater solutions (containing a mixture of anions) Cl- dominates the process [27].…”
Section: Resultsmentioning
confidence: 99%
“…It was 250 and 316.6 ppb in bigger and smaller crevices, respectively. Xu et al have reported that ion promotes crevice corrosion in carbon steel more compared to Cl − in single ion solutions whereas; in groundwater solutions (containing a mixture of anions) Cl- dominates the process [27].…”
Section: Resultsmentioning
confidence: 99%
“…Before testing, the samples were degreased with ethanol and deionized water. A solution, with a similar composition to the groundwater in the North Mountain in Gansu, China, 24,25 was used as the standard solution, and contained 0.2051 mol l −1 Cl − , 0.0775 mol l −1 SO 4 2− , and 0.0167 mol l −1 HCO 3 − (pH 7.23). As shown in Table II, experimental solutions with different chemical compositions were prepared to investigate the effects of chemical compositions (except Cl − , which has been reported in an earlier study 26 ) of underground water on the corrosion behavior of low-nickel stainless steel.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…This declining is perhaps because of the stability of ferric oxide film that formed after corrosion occurrence. The phenomena is known for corrosion inhibitor behavior of anions in aqueous solutions (Xu et al 2017). In general, it is noticed that the corrosion rate is highly reduced in the solutions contain hexamine or aniline inhibitor.…”
Section: Effect Of Corrosion Inhibitorsmentioning
confidence: 99%